Environmental Pollutions on Scholar Advocacy Program - Nor Fadzillah, Zulkipli (2017)
National Professor Council (MPN) together with Radio Televisyen Malaysia (RTM) and Universiti Malaysia Pahang organized Scholar Advocacy Program with the title “Environmental Pollution : Is There Any Solution?” that took place at UMP Gambang Astaka Hall. This program aims to discuss national issue on environmental pollutions.